Influence of Mouth Motion Fatigue and Thermal Cycling on the Marginal Accuracy and Fracture Resistance of Lithium Disilicate and Zirconia Partial Crowns: A Systematic Review and Meta-Analysis - Mistry, Gaurang S.; Sardar, Charushila S.; Rathod, Asha M.; Bachhav, Mayuri D.; Pokharkar, Amit B.; Dua, Ishita (Journal of Neonatal Surgery, 2026)
The present systematic review and meta-analysis aimed to evaluate the effect of mouth motion fatigue and thermal cycling on the marginal accuracy and fracture resistance of lithium disilicate and zirconia partial crowns. A comprehensive search was conducted across PubMed, Cochrane Library, and Google Scholar, and 12 studies were included for qualitative synthesis and meta-analysis. The meta-analysis revealed a pooled effect size of 0.222 with a standard error of 0.015 and a 95% confidence interval of 0.193–0.251, indicating a consistent and moderate effect of thermo-mechanical aging on crown performance. Heterogeneity among the studies was negligible (I² = 0%), justifying the use of a fixed-effects model. Lithium disilicate demonstrated favorable marginal adaptation and esthetic properties, while zirconia exhibited superior fracture resistance and mechanical strength under fatigue and thermal stress. Although both materials showed clinical promise, zirconia held a slight mechanical advantage. However, the high risk of bias across studies and the predominance of in vitro designs underscore the need for standardized protocols and long-term clinical research. These findings support material-specific clinical decision-making and reinforce the relevance of fatigue and thermal testing in restorative material evaluation